Phase-change heat-conducting composite material with core-sheath structure and coaxial DIW printing preparation method of phase-change heat-conducting composite material

Through coaxial DIW printing technology and bio-based polyphenol/Ag+ assisted ball milling method to peel off h-BN, a phase-change thermally conductive composite material with a core sheath structure is prepared, which solves the problem of easy leakage and complex packaging of phase-change materials, and achieves efficient thermal management performance and cycling stability.

CN119529770APending Publication Date: 2025-02-28JIANGNAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411717510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing phase change materials are prone to leakage and lack flexibility during use, which limits their application in the field of thermal management, and the packaging process is complex, making it difficult to develop flexible packaging methods.

Method used

Using coaxial DIW printing technology, bio-based polyphenol/Ag+ assisted ball milling peel off h-BN, bio-based polyphenol functionalized and Ag nanoparticles modified BNNS was prepared. As a sheath ink, combined with end vinyl polydimethylsiloxane PDMS, an Ag-BNNS/PDMS-S sheath layer was formed, and PEG2000 was tightly encapsulated as the core layer, and a phase-change thermal composite material with a core sheath structure was constructed by ultraviolet light assisted coaxial printing.

Benefits of technology

The effective packaging of PEG2000 is realized, and annular thermal conductivity structure and a dense three-dimensional thermal conductivity network are constructed, and the thermal conductivity and latent thermal conductivity of phase-change thermal conductivity composite materials are improved, so as to obtain materials with good thermal conductivity and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529770A_ABST
    Figure CN119529770A_ABST
Patent Text Reader

Abstract

The invention discloses a phase-change heat-conducting composite material with a core-sheath structure and a coaxial DIW printing preparation method of the phase-change heat-conducting composite material with the core-sheath structure, h-BN is stripped through bio-based polyphenol / Ag < + > assisted ball milling, BNNS (Ag-BNNS) functionalized by bio-based polyphenol and modified by Ag nanoparticles is prepared by utilizing the reducibility of the bio-based polyphenol to metal ions, the transverse size of the BNNS is about 1-3 microns, and the thickness of the BNNS is about 5 nm. A phase-change heat-conducting composite material with a core-sheath structure is constructed through coaxial DIW printing assisted by ultraviolet light, Ag-BNNS / polydimethylsiloxane (PDMS) is used as a packaging layer (sheath layer), and polyethylene glycol is used as a core material phase-change material. By means of coaxial printing, packaging of PEG2000 is achieved, meanwhile, an annular heat conduction structure is constructed, Ag-BNNS is further oriented under the extrusion effect to form a compact heat conduction outer layer with a three-dimensional heat conduction network, and the phase change heat conduction composite material shows the high heat conduction coefficient (0.70 W.m <-1 >. K <-1 >) and the high phase change enthalpy (65.4 J / g).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field, and in particular relates to a phase-change thermally conductive composite material with a core-sheath structure and a coaxial DIW printing preparation method thereof. Background Art

[0002] Phase change material is a kind of "passive" thermal management material. It is widely used in the field of thermal management due to its excellent latent heat characteristics and isothermal properties during the phase change process. Therefore, introducing phase change materials into polymer-based thermal conductive composites is expected to further improve their thermal management capabilities. The organic phase change material polyethylene glycol (PEG) is favored for its suitable phase change temperature, high phase change latent heat, good chemical and thermal stability. However, phase change materials have problems such as easy leakage and lack of flexibility during use, which limits their application in the field of thermal management. Methods such as microencapsulation, porous skeleton adsorption and melt blending have been widely used to solve the leakage problem during the phase change process, but most encapsulation processes are still relatively complicated, and the development of flexible encapsulation methods is still a huge challenge.

[0003] DIW (Direct Ink Writing) is a 3D printing technology that deposits liquid ink directly onto a printing substrate through a precisely controlled nozzle to build a three-dimensional structure.

[0004] Coaxial DIW printing technology is an advanced additive manufacturing method that combines traditional DIW technology with coaxial nozzle design to achieve higher precision and more complex 3D printing works. Coaxial DIW printing technology is compatible with a variety of different printing materials and can be used to manufacture composite materials with different physical properties and functions. Due to the high precision and multi-material compatibility of coaxial DIW printing technology, it can be used to manufacture 3D objects with complex internal structures and shapes. This is very difficult or even impossible for traditional manufacturing methods.

[0005] Therefore, it is extremely important to use DIW printing technology in the research of molding of organic thermal conductive phase change material composites. Summary of the invention

[0006] Purpose of the invention: In order to overcome the shortcomings of the prior art, the present invention provides a phase-change thermal conductive composite material with a core-sheath structure and a coaxial DIW printing preparation method thereof, which is based on DIW printing technology and utilizes the technology to more flexibly encapsulate phase change materials to prepare phase change thermal conductive composite materials. First, bio-based polyphenol / Ag +The bio-based polyphenol functionalized and Ag nanoparticle-modified BNNS (Ag-BNNS) was prepared by ball-milling h-BN, and the Ag-BNNS / PDMS-S ink suitable for DIW printing was prepared with end-vinyl polydimethylsiloxane (PDMS) as the polymer matrix. Finally, Ag-BNNS / PDMS-S was used as the encapsulation layer (sheath layer) and PEG2000 was used as the core layer phase change material. The phase change thermal conductive composite material with a core-sheath structure was constructed by UV-assisted coaxial printing. Through coaxial printing, a ring-shaped thermal conductive structure was constructed on a macro scale. Furthermore, Ag-BNNS can form a dense three-dimensional thermal conductive network, which can jointly improve the thermal conductivity of the phase change thermal conductive composite material, and at the same time realize the effective encapsulation of PEG2000, and finally obtain a phase change thermal conductive composite material with good thermal conductivity and latent heat performance.

[0007] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is:

[0008] The first object of the present invention is to provide a modified boron nitride nanosheet, wherein the surface of the modified boron nitride nanosheet is functionalized with bio-based polyphenol and modified with Ag nanoparticles, which is denoted as Ag-BNNS.

[0009] Optionally, in some embodiments of the present invention, the bio-based polyphenols include at least one of catechol, apple polyphenols, tannins, and flavonoids.

[0010] Optionally, in some embodiments of the present invention, the modified boron nitride nanosheets have a lateral size of 1 to 3 μm and a thickness of 5 to 20 nm.

[0011] The second object of the present invention is to provide a method for preparing modified boron nitride nanosheets, comprising the following steps: dispersing h-BN in Ag + The aqueous solution and the bio-based polyphenol aqueous solution are mixed, ball milled, centrifuged and dried to obtain modified boron nitride nanosheets Ag-BNNS.

[0012] Optionally, in some embodiments of the present invention, in the mixed solution, 0.02-0.1 g / mL Ag + The aqueous solution is mixed with a 0.1-0.4 g / mL bio-based polyphenol aqueous solution in a volume ratio of 1:1.

[0013] Further optionally, in some embodiments of the present invention, in the mixed solution, 0.04 g / mL Ag + The aqueous solution was mixed with a 0.2 g / mL bio-based polyphenol aqueous solution in a volume ratio of 1:1.

[0014] Optionally, in some embodiments of the present invention, the solubility of h-BN in the above-mentioned mixed solution is 0.05-0.5 mg / L.

[0015] Further optionally, in some embodiments of the present invention, the solubility of h-BN in the above-mentioned mixed solution is 0.2-0.5 mg / L.

[0016] Optionally, in some embodiments of the present invention, the dispersing includes uniform dispersion by ultrasound for 20-120 min.

[0017] Further optionally, in some embodiments of the present invention, the dispersing includes uniform dispersion by ultrasonication for 20 minutes.

[0018] Optionally, in some embodiments of the present invention, the ball milling includes ball milling in a ball mill at 200-500 rpm for 12-48 hours.

[0019] Further optionally, in some embodiments of the present invention, the ball milling includes ball milling at 500 rpm for 24 hours in a ball mill.

[0020] Optionally, in some embodiments of the present invention, the centrifugation includes centrifugation at 9000-12000 rpm for 10-20 min.

[0021] Further optionally, in some embodiments of the present invention, the centrifugation includes centrifugation at 9000 rpm for 15 min.

[0022] Optionally, in some embodiments of the present invention, the drying includes drying at 60-100° C. for 10-24 h.

[0023] Further optionally, in some embodiments of the present invention, the drying includes drying at 70° C. for 24 hours.

[0024] The third object of the present invention is to provide the modified boron nitride nanosheets as described above or prepared by the method as described above for use in thermal conductive materials.

[0025] A fourth object of the present invention is to provide a phase-change thermally conductive composite material having a core-sheath structure, the phase-change thermally conductive composite material comprising a sheath layer and a core layer, wherein the core layer is encapsulated in the sheath layer, wherein:

[0026] The core layer is made of phase change material.

[0027] The sheath layer is an encapsulation layer of Ag-BNNS / PDMS-S, and the Ag-BNNS / PDMS-S is a sheath layer ink prepared by modified boron nitride nanosheets Ag-BNNS and terminal vinyl polydimethylsiloxane PDMS. The modified boron nitride nanosheets Ag-BNNS are modified boron nitride nanosheets as described above, or prepared by any of the methods described above.

[0028] Optionally, in some embodiments of the present invention, the phase change material includes one or more of polyethylene glycol PEG2000, polyethylene glycol PEG1000, paraffin, long-chain alkane, etc.

[0029] Optionally, in some embodiments of the present invention, in the phase-change thermal conductive composite material, the encapsulation rate of the phase-change material reaches 20%-80%.

[0030] Further optionally, in some embodiments of the present invention, in the phase-change thermal conductive composite material, the encapsulation rate of the phase-change material reaches 40-50%.

[0031] Optionally, in some embodiments of the present invention, the thermal conductivity of the phase-change thermally conductive composite material is ≥ 0.60 W·m -1 ·K -1 , further, thermal conductivity ≥ 0.65 W·m -1 ·K -1 .

[0032] Optionally, in some embodiments of the present invention, the phase change enthalpy ΔH of the phase change thermal conductive composite material is m ≥40J / g, further, phase change enthalpy ΔH m ≥68J / g.

[0033] A fifth object of the present invention is to provide a coaxial DIW printing preparation method of a phase change thermal conductive composite material having a core-sheath structure, comprising the following steps:

[0034] (1) Preparation of sheath ink

[0035] A polymer matrix ink for DIW is prepared by preparing vinyl-terminated polydimethylsiloxane (PDMS) and an active diluent, and its rheological properties are adjusted by using fumed silica, which is recorded as PDMS-S; modified boron nitride nanosheets (Ag-BNNS), a photoinitiator and a thermal initiator are added to the PDMS-S, and the mixture is placed in a ball mill and mixed evenly to prepare a sheath ink for DIW printing, which is recorded as Ag-BNNS / PDMS-S; the modified boron nitride nanosheets (Ag-BNNS) are any of the above, or are modified boron nitride nanosheets prepared by any of the above methods;

[0036] (2) Preparation of phase change thermal conductive composite materials

[0037] The sheath ink Ag-BNNS / PDMS-S is loaded into the outer channel of the coaxial printing needle, and the phase change material enters the inner channel of the coaxial printing needle through the injection pump and is printed in a DIW 3D printer. During the printing process, the extruded sheath ink is in-situ cured by ultraviolet light curing to obtain a phase change thermal conductive composite material with a core-sheath structure with phase change material as the core layer and Ag-BNNS / PDMS-S as the encapsulation layer.

[0038] Optionally, in some embodiments of the present invention, in step (1), the mass ratio of the vinyl-terminated polydimethylsiloxane PDMS to the reactive diluent is 2:1-1:2.

[0039] Further optionally, in some embodiments of the present invention, in step (1), the mass ratio of the vinyl-terminated polydimethylsiloxane PDMS to the reactive diluent is 1:1.

[0040] Optionally, in some embodiments of the present invention, in step (1), the active diluent includes at least one of any photosensitive monomers such as IBOA, TPGDA, GMA, etc.

[0041] Optionally, in some embodiments of the present invention, in step (1), the amount of modified boron nitride nanosheets Ag-BNNS in the sheath ink is 20-40 wt %.

[0042] Further optionally, in some embodiments of the present invention, in step (1), the amount of modified boron nitride nanosheets Ag-BNNS in the sheath ink is 30 wt %.

[0043] Optionally, in some embodiments of the present invention, in step (1), the photoinitiator includes at least one of 819, 784, 1173, etc.

[0044] Optionally, in some embodiments of the present invention, in step (1), the photoinitiator is 1-4 wt % of the reactive diluent.

[0045] Further optionally, in some embodiments of the present invention, in step (1), the photoinitiator is 2 wt % of the active diluent.

[0046] Optionally, in some embodiments of the present invention, in step (1), the thermal initiator includes at least one of BPO, AIBN, ABVN, etc.

[0047] Optionally, in some embodiments of the present invention, in step (1), the thermal initiator is 1-3 wt % of PDMS.

[0048] Further optionally, in some embodiments of the present invention, in step (1), the thermal initiator is 2 wt % of PDMS.

[0049] Optionally, in some embodiments of the present invention, in step (2), the outside of the injection pump has a heating jacket, and the temperature is set to 50-100° C., so that the phase change material is heated to a liquid so that it can be extruded from the coaxial printing needle.

[0050] Further optionally, in some embodiments of the present invention, in step (2), the outside of the injection pump has a heating jacket, and the temperature is set to 70°C.

[0051] Optionally, in some embodiments of the present invention, in step (2), the ratio of the phase change material to Ag-BNNS / PDMS-S is 1:4-4:1.

[0052] Further optionally, in some embodiments of the present invention, in step (2), the ratio of the phase change material to Ag-BNNS / PDMS-S is 2:3.

[0053] Optionally, in some embodiments of the present invention, in step (2), the printed phase change thermal conductive composite material is further cured by keeping the temperature at 80-120° C. for 1-5 hours.

[0054] Further optionally, in some embodiments of the present invention, in step (2), the printed phase change thermal conductive composite material is further cured by keeping it at 120° C. for 2 hours.

[0055] A sixth object of the present invention is to provide a phase-change thermally conductive composite material with a core-sheath structure as described above or prepared by any of the methods described above for application in the field of thermal management.

[0056] Optionally, in some embodiments of the present invention, the thermal management includes battery thermal management, building energy conservation, communication equipment heat dissipation, etc.

[0057] Beneficial effects: The present invention provides a phase-change thermal conductive composite material with a core-sheath structure and a coaxial DIW printing preparation method thereof, prepares Ag-BNNS functionalized with bio-based polyphenols and in-situ reduced and modified with Ag nanoparticles, and prepares a phase-change thermal conductive composite material with a core-sheath structure such as PEG@Ag-BNNS / PDMS-S through coaxial DIW printing design.

[0058] The morphology, structure and chemical composition of the prepared Ag-BNNS were characterized, the rheological properties of the ink were tested, and the thermal conductivity, phase change characteristics and cycle stability of the composite material were systematically studied. The conclusions are as follows:

[0059] (1) After ball milling of bio-based polyphenols such as apple polyphenols / Ag+ Ag-BNNS functionalized with bio-based polyphenols and modified with Ag nanoparticles were prepared by assisted ball milling exfoliation. The lateral size of the Ag-BNNS was about 1 to 3 μm and the thickness was about 5 nm. The functionalized Ag-BNNS could effectively improve the compatibility between the filler and the polymer matrix. The Ag-BNNS modified with Ag nanoparticles could further form a dense and effective three-dimensional thermal conductive network, thereby improving the thermal conductivity of the composite material.

[0060] (2) A phase-change thermal conductive composite material with a core-sheath structure was successfully prepared by coaxial DIW printing technology. The Ag-BNNS / PDMS-S in the sheath layer can effectively encapsulate PEG2000. The composite material has a ring-shaped thermal conductive structure and a dense thermal conductive sheath layer. When the encapsulated PEG2000 content is 40.7wt%, the thermal conductivity of the composite material can reach 0.70W·m -1 ·K -1 , and has a high phase change enthalpy (65.4J / g) and excellent cycle stability.

[0061] (3) Complex-shaped composite materials were prepared using coaxial DIW printing technology, which successfully achieved the encapsulation of the core phase change material and the construction of the shell thermal conductive network. The prepared phase change thermal conductive composite materials have the performance of both phase change thermal conductivity and filler-reinforced blended thermal conductive materials, and show excellent thermal management capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 Schematic diagram of the preparation process of Ag-BNNS and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite materials.

[0063] Figure 2 The physical property test results of Ag-BNNS, including (a) SEM images of h-BN and (b) Ag-BNNS, (c) TEM image of Ag-BNNS, (d) AFM image of Ag-BNNS and its thickness curve, (e, f) XRD spectra of h-BN and A-BNNS.

[0064] Figure 3 Rheological properties of sheath inks of different phase change thermal conductive composite materials, including (a) viscosity of different sheath inks, (b) dynamic modulus (solid line: storage modulus; dashed line: loss modulus), (c) cross-sectional photo of 3D printed PEG@h-BN / PDMS-S, (d) appearance photo of 3D printed PEG@h-BN / PDMS-S, (e) appearance photo of PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite material.

[0065] Figure 4The thermal conductivity test results of phase change thermal conductive composite materials, including (a) thermal conductivity of different phase change thermal conductive composite materials, (b, c) SEM images of the cross section of a single PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite material and (d) schematic diagram of thermal conduction of coaxial phase change thermal conductive composite materials.

[0066] Figure 5 The thermal management capability of the phase-change thermal conductive composite material, including (a) infrared thermal imaging of PDMS-S and PEG@Ag-BNNS / PDMS-S phase-change thermal conductive composite materials placed on a heating platform, and (b) a graph showing the surface temperature change of PDMS-S and PEG@Ag-BNNS / PDMS-S phase-change thermal conductive composite materials over time.

[0067] (c) Schematic diagram of the heat dissipation device.

[0068] Figure 6 Phase change properties of phase change thermal conductive composite materials, including (a) DSC curves of PEG2000 and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite materials, (b) DSC curves of PEG2000 and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite materials before and after 50 hot and cold cycles and their cyclic enthalpy retention rates. DETAILED DESCRIPTION

[0069] The invention discloses a phase-change thermal conductive composite material with a core-sheath structure and a coaxial DIW printing preparation method thereof, wherein bio-based polyphenol / Ag + By using ball-milling to exfoliate h-BN, bio-based polyphenols including apple polyphenols were used to reduce metal ions, and bio-based polyphenols functionalized and Ag nanoparticle-modified BNNS (Ag-BNNS) were prepared. The lateral size was about 1-2 μm and the thickness was about 5 nm. A phase-change thermal conductive composite material with a core-sheath structure was constructed by UV-assisted coaxial DIW printing. Ag-BNNS / polydimethylsiloxane (PDMS) was the encapsulation layer (sheath layer), and polyethylene glycol (such as PEG2000) was the core phase change material. Coaxial printing not only achieved the encapsulation of PEG2000, but also constructed a ring-shaped thermal conductive structure. Ag-BNNS was further oriented under extrusion to form a dense thermal conductive outer layer with a three-dimensional thermal conductive network, which made the phase-change thermal conductive composite material show a higher thermal conductivity (0.70 W·m -1 ·K -1 ) and higher phase change enthalpy (65.4 J / g).

[0070] Specifically, Figure 1 The figure shows the schematic diagram of the preparation process of Ag-BNNS and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite materials, which includes the following steps:

[0071] First, prepare modified boron nitride nanosheets, specifically including the following steps: disperse h-BN in Ag + The aqueous solution and the vinyl-terminated polyphenol aqueous solution are mixed, ball-milled, centrifuged and dried to obtain modified boron nitride nanosheets Ag-BNNS.

[0072] Second, coaxial DIW printing is used to prepare a phase change thermal conductive composite material with a core-sheath structure, which specifically includes the following steps:

[0073] (1) Preparation of sheath ink

[0074] The polymer matrix is ​​prepared by preparing vinyl-terminated polydimethylsiloxane (PDMS) and an active diluent, and its rheological properties are adjusted by using fumed silica, which is recorded as PDMS-S; modified boron nitride nanosheets Ag-BNNS, a photoinitiator and a thermal initiator are added to the PDMS-S, placed in a ball mill, and mixed evenly to prepare a sheath ink for DIW printing, which is recorded as Ag-BNNS / PDMS-S; the modified boron nitride nanosheets Ag-BNNS are any of the above, or modified boron nitride nanosheets prepared by any of the above methods;

[0075] (2) Preparation of phase change thermal conductive composite materials

[0076] The sheath ink Ag-BNNS / PDMS-S is loaded into the outer channel of the coaxial printing needle, and the phase change material enters the inner channel of the coaxial printing needle through the injection pump and is printed in a DIW 3D printer. During the printing process, the extruded sheath ink is in-situ cured by ultraviolet light curing to obtain a phase change thermal conductive composite material with a core-sheath structure with phase change material as the core layer and Ag-BNNS / PDMS-S as the encapsulation layer.

[0077] Example

[0078] The present invention is further described below in conjunction with the accompanying drawings and examples. The following examples are described in detail using apple polyphenols as an example, and the present invention can be better understood based on the following examples. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0079] Example 1 Preparation of Apple Polyphenol Functionalized and Ag Nanoparticle Modified BNNS (Ag-BNNS)

[0080] In the embodiment of the present invention, apple polyphenol / Ag +The h-BN was exfoliated by ball milling and the reducing property of apple polyphenols on metal ions was utilized to prepare BNNS functionalized with apple polyphenols and modified with Ag nanoparticles (Ag-BNNS). The specific method is as follows:

[0081] (1) Apple polyphenols were completely dissolved in deionized water to prepare a 0.2 g / mL apple polyphenol aqueous solution, and AgNO 3 Completely dissolved in deionized water to prepare 0.04 g / mL Ag + aqueous solution, mixing it with apple polyphenol aqueous solution at a ratio of 1:1 to obtain a mixed solution, and ultrasonically dispersing 0.2 g h-BN in the mixed solution for 20 min to obtain a dispersion;

[0082] (2) The dispersion was then transferred to an agate jar containing 50 g of agate balls (25 g of agate balls with diameters of 12 mm and 6 mm) and milled in a planetary ball mill at 500 rpm for 24 h (forward rotation for 1 h, stop for 0.5 h, reverse rotation for 1 h, stop for 0.5 h, and repeat for 24 h);

[0083] (3) The resulting mixture was placed in a centrifuge tube and centrifuged at 9000 rpm for 15 min to precipitate it. It was then washed several times with deionized water and dried in a vacuum oven at 70 °C for 24 h to obtain apple polyphenol-functionalized and Ag nanoparticle-modified BNNS (Ag-BNNS).

[0084] Figure 1 Schematic diagram of the preparation process of modified boron nitride nanosheets Ag-BNNS. As shown in the figure, in the present invention, bio-based polyphenols such as apple polyphenols and Ag + are added at the same time, because Ag + Due to its small size, it can quickly diffuse into the interlayer of h-BN. However, due to its large molecular size, apple polyphenols need to be intercalated by ultrasonic ball milling. During this process, apple polyphenol molecules also react with anions, and the generated elemental silver can also play a role in exfoliating h-BN. Elemental silver is similar to a very small ball milling bead. Therefore, during the ball milling process, mechanical ball milling can promote the intercalation of apple polyphenol molecules and Ag. + The interaction and intercalation between h-BN layers and the shear force generated by ball milling further exfoliate the h-BN. Apple polyphenols can modify BNNS through covalent modification of hydroxyl groups and strong π-π interaction of benzene ring structures. At the same time, since the polyphenol structure in apple polyphenols has the ability to reduce metal ions, Ag can be further exfoliated during the exfoliation and functionalization of h-BN. +The Ag-BNNS was reduced to Ag nanoparticles and in situ deposited on the surface of BNNS to obtain apple polyphenol functionalized and Ag nanoparticle-modified BNNS (Ag-BNNS). The functionalization of Ag-BNNS is beneficial to improve its compatibility with the polymer matrix and reduce the interfacial thermal resistance. At the same time, the Ag nanoparticles on its surface can serve as a "bridge" connecting adjacent Ag-BNNS, which is conducive to forming a three-dimensional thermal conductive network and improving the thermal conductivity of the composite material.

[0085] Performance characterization test results of modified boron nitride nanosheets Ag-BNNS:

[0086] Specifically, the morphology and structure of h-BN before and after peeling were characterized by SEM, TEM, AFM, XRD and Raman methods, and the results are as follows.

[0087] SEM images of h-BN before and after peeling Figure 2 a. Figure 2 As shown in b, Figure 2 The SEM image of the original h-BN block is shown in a. The original h-BN is a layered structure with a lateral size of about 20 to 30 μm and a thickness of about 1 to 2 μm. Its surface is relatively smooth and its edges are relatively flat. Figure 2 As shown in (b), the Ag-BNNS obtained by mechanical ball milling is significantly thinner, the lateral size is reduced to about 1-3 μm, the edges are slightly curled, and a large number of Ag nanoparticles are deposited on the surface.

[0088] TEM images of the Ag-BNNS after exfoliation are shown in Figure 2. Figure 2 As shown in c, from the TEM image ( Figure 2 c) It can be seen that Ag-BNNS is thin and transparent, and a large number of Ag nanoparticles are distributed on the surface, indicating that Ag + Apple polyphenols were successfully reduced to Ag nanoparticles and in situ deposited on the surface of Ag-BNNS.

[0089] The AFM images of the peeled Ag-BNNS and the corresponding thickness curves are shown in Figure 2. Figure 2 As shown in (d), the lateral size of the Ag-BNNS is about 1.5 μm and the thickness is about 5 nm, indicating the successful exfoliation of the Ag-BNNS.

[0090] The XRD patterns of h-BN before and after peeling are shown in Figure 2. Figure 2 e. Figure 2 f, it can be seen from the XRD results that compared with h-BN, the (002) diffraction peak intensity of the peeled Ag-BNNS is significantly reduced and moves to a lower angle (from 27.17° to 27.08°), indicating that the interlayer distance of Ag-BNNS is increased, proving that apple polyphenol molecules and Ag +The intercalation effect further proves that h-BN is effectively exfoliated into Ag-BNNS. In addition, new characteristic peaks appear in the XRD spectrum of Ag-BNNS. The characteristic peaks at 38.51°, 64.68° and 77.52° correspond to the (111), (220) and (311) crystal planes of Ag nanoparticles, respectively, indicating the successful synthesis of surface Ag nanoparticles.

[0091] Example 2 Preparation of a phase-change thermally conductive composite material having a core-sheath structure

[0092] (1) Preparation of DIW printing ink

[0093] The polymer matrix ink for DIW was prepared with a vinyl-terminated polydimethylsiloxane (PDMS) oligomer and an active diluent (IBOA) in a mass ratio of 1:1, and then its rheological properties were adjusted with fumed silica, which was recorded as PDMS-S. Then, Ag-BNNS (30wt% of the ink), a photoinitiator (819, 2wt% of the active diluent) and a thermal initiator (BPO, 2wt% of PDMS) were added, and the mixture was placed in a ball mill and mixed evenly by a high-speed disperser to prepare a sheath ink for DIW printing, which was recorded as Ag-BNNS / PDMS-S.

[0094] (2) Preparation of composite materials

[0095] Before DIW printing, the ink was defoamed by centrifugation, and then the syringe filled with ink was installed in the DIW 3D printer for printing.

[0096] The printer has a coaxial printing needle, the sheath ink Ag-BNNS / PDMS-S enters the external channel of the coaxial printing needle, the syringe containing PEG2000 is covered with a heating sleeve, the temperature is set to 70°C, PEG2000 is heated to a liquid so that it can be extruded from the needle, and PEG2000 enters the internal channel of the needle through a syringe pump. During the printing process, the extruded ink is cured in situ by ultraviolet light curing, the ultraviolet light irradiation band is 330-530nm, and then the obtained composite material is kept at 120°C for 2h for further cross-linking and curing, and the composite material is recorded as PEG@Ag-BNNS / PDMS-S. The vinyl-terminated polydimethylsiloxane has an end group before curing, and becomes polydimethylsiloxane after curing, which is recorded as PDMS in the present invention. In the present invention, the flow rate has no effect, and the outer layer of DIW only needs to wrap the inner layer of PEG phase change material with a polymer matrix ink, so the flow rate of the coaxial printing needle is not limited in the present invention, and all belong to the protection scope of the present invention.

[0097] Phase change thermal conductive composite materials with core-sheath structure were prepared by coaxial printing technology. The core layer (PEG2000) and sheath ink (Ag-BNNS / PDMS-S) entered the inner and outer channels of the coaxial printing needle respectively, and the sheath ink was quickly formed by in-situ photocuring. Since the Ag-BNNS modified with deposited Ag nanoparticles is dark, the sheath cannot be completely cured after light exposure, so further thermal curing is required to make it completely cured. Finally, the phase change material is tightly encapsulated in the sheath so that it will not leak during use. At the same time, through coaxial printing, the sheath ink constructs a ring-shaped thermal conductive structure on a macroscopic level, and the Ag nanoparticles bridge adjacent Ag-BNNS on a microscopic level to form a dense three-dimensional thermal conductive network, which together improves the thermal conductivity of the phase change thermal conductive composite material.

[0098] Comparative Example 1: Unmodified h-BN is used to prepare a phase change thermal conductive composite material with a core-sheath structure

[0099] The method is the same as that of Example 2, except that the sheath ink is h-BN / PDMS-S, and the specific preparation method thereof is as follows:

[0100] (1) Preparation of unmodified DIW printing ink

[0101] The polymer matrix was prepared by mixing vinyl-terminated polydimethylsiloxane (PDMS) and active diluent (IBOA) in a mass ratio of 1:1, and then its rheological properties were adjusted with fumed silica, which was recorded as PDMS-S. Then h-BN (30wt% of the ink), photoinitiator (819, 2wt% of the active diluent) and thermal initiator (BPO, 2wt% of PDMS) were added, and the mixture was placed in a ball mill and mixed evenly by a high-speed disperser to prepare a sheath ink for DIW printing, which was recorded as h-BN / PDMS-S.

[0102] (2) Preparation of unmodified composite materials

[0103] Before DIW printing, the ink was defoamed by centrifugation, and then the syringe filled with ink was installed in the DIW 3D printer for printing.

[0104] The printer has a coaxial printing needle, the sheath ink h-BN / PDMS-S enters the external channel of the needle, the syringe containing PEG2000 is covered with a heating sleeve, and the temperature is set to 70°C, so that PEG2000 is heated to a liquid so that it can be extruded from the needle, and PEG2000 enters the internal channel of the needle through a syringe pump. During the printing process, the extruded ink is in-situ cured by ultraviolet curing, and then the obtained composite material is further cured by keeping it at 120°C for 2 hours. The composite material is recorded as PEG@h-BN / PDMS-S.

[0105] Test example Performance characterization of phase change thermal conductive composite materials

[0106] (1) Rheological properties of sheath ink

[0107] For UV-assisted coaxial DIW printing, ink design plays a pivotal role. The ink must have good printability and conformality to be smoothly extruded from the nozzle and quickly cured in situ to obtain a coaxial structure with high conformality.

[0108] Rheological properties of sheath inks of different phase change thermal conductive composite materials are as follows: Figure 3 shown.

[0109] Pure PDMS resin exhibits Newtonian fluid characteristics, and its apparent viscosity basically does not change with the change of shear rate. Its storage modulus (G′) is lower than the loss modulus (G″) and does not change with the change of shear force. Pure PDMS ink exhibits Newtonian fluid characteristics under any shear force and has good fluidity. This shows that during the DIW extrusion process, pure PDMS resin is easily squeezed out of the nozzle, but collapses immediately after leaving the nozzle, lacking self-support and conformal ability. Therefore, it is necessary to add 2-10wt% fumed silica to adjust its rheological properties.

[0110] from Figure 3 As can be seen in a, with the SiO 2 With the addition of , the viscosity of the ink increases sharply and decreases with the increase of shear rate, showing shear thinning behavior, indicating that the ink can be squeezed out of the coaxial needle smoothly without clogging. At the same time, under high shear stress, the G′ of PDMS-S ink is greater than G″ ( Figure 3 b), indicating that the ink has good self-supporting ability and good self-conserving ability after leaving the nozzle. After adding 30wt% thermal conductive filler (h-BN or Ag-BNNS), the viscosity of the ink further increased, but the viscosity of Ag-BNNS / PDMS-S was higher than that of h-BN / PDMS-S. This is mainly because the addition of fillers to the resin system hinders the movement of the molecular chain, and the Ag nanoparticles on the surface of Ag-BNNS further hinder the movement of the molecular chain, causing the viscosity to increase. However, the ink always maintains the rheological properties of shear thinning, and at high shear rates, the G′ of the ink is greater than G″, showing good printability and conformality, and in-situ photocuring further enhances the conformality of the ink.

[0111] Figure 3 ce are the cross-section (3c) and appearance (3d) of PEG@h-BN / PDMS-S and the appearance (3e) of PEG@Ag-BNNS / PDMS-S printed by UV-assisted coaxial DIW, and the printed devices show good precision. Figure 4It can be seen from the cross-sectional photographs of the composite material shown in 4b and 4c that PEG2000 is tightly encapsulated in the coaxial structure so that it will not leak during use.

[0112] (2) Thermal conductivity of composite materials:

[0113] The thermal conductivity of the phase change thermal conductive composite material prepared in Example 2 and Comparative Example 1 is as follows: Figure 4 As shown in a.

[0114] The thermal conductivity of pure PA-S is 0.06 W·m -1 ·K -1 After adding 30wt% h-BN, the thermal conductivity of h-BN / PDMS-S composite material increased to 0.79W·m -1 ·K -1 At this time, more fillers have formed a denser heat conduction path in the composite material.

[0115] At the same filler content, the thermal conductivity of Ag-BNNS / PDMS-S composite material can reach 0.88 W·m -1 ·K -1 , which increased by 11.4% compared with h-BN / PDMS-S, indicating that the peeled apple polyphenol-modified and Ag nanoparticle-modified Ag-BNNS can effectively improve the thermal conductivity of the composite material.

[0116] There are two main aspects to improve the thermal conductivity of composite materials:

[0117] (a) Compared with h-BN, the Ag-BNNS functionalized with apple polyphenols has better compatibility with the polymer matrix, which improves its dispersibility in the composite material, helps to reduce agglomeration, reduce the interfacial thermal resistance and thus improve the thermal conductivity of the composite material;

[0118] (b) The surface-deposited Ag nanoparticles create additional contacts between Ag-BNNSs, which can act as bridges to connect adjacent fillers and form a three-dimensional thermal conductive network, thereby improving the thermal conductivity of the composite.

[0119] Furthermore, when PEG2000 was added to the Ag-BNNS / PDMS-S composite, the thermal conductivity of PEG2000 itself was low (0.13 W·m -1 ·K -1 ), which reduced the thermal conductivity of the composite material to a certain extent. The thermal conductivity of the obtained PEG@h-BN / PDMS-S composite material was 0.60 W·m -1 ·K -1 .

[0120] When Ag-BNNS / PDMS-S is used as the sheath layer, the thermal conductivity of the phase change thermal conductive composite material PEG@Ag-BNNS / PDMS-S can be increased to 0.70 W·m -1 ·K -1 , which is mainly attributed to the formation of a dense thermal conductive outer layer in the composite material of apple polyphenols and Ag nanoparticles modified Ag-BNNS.

[0121] In order to better illustrate the improvement of thermal conductivity of phase change thermal conductive composite materials, the thermal conduction mechanism was further elaborated and electron microscopy tests were performed on the phase change thermal conductive composite materials.

[0122] from Figure 4 It can be seen from the electron microscope photos shown in b and 4c that the phase change thermal conductive material with a core-sheath structure was successfully prepared by coaxial printing technology. PEG2000 was encapsulated in the sheath layer. Under the action of DIW extrusion shear force, the flake h-BN was oriented along the extrusion direction to form a dense thermal conductive sheath layer, forming a ring-shaped three-dimensional thermal conductive structure, and the heat flow was transferred along the thermal conductive sheath layer ( Figure 4 d). Furthermore, the nanoparticles deposited on the surface of Ag-BNNS can bridge adjacent fillers to form a dense and effective three-dimensional thermal conductive network, reduce interfacial thermal resistance, reduce phonon heat dissipation, and effectively improve the thermal conductivity of the composite material. Therefore, compared with PEG@h-BN / PDMS-S, PEG@Ag-BNNS / PDMS-S has a denser and more effective thermal conductive sheath layer, showing better thermal conductivity.

[0123] (3) Thermal management capabilities of phase change thermally conductive composite materials

[0124] In order to test the thermal management ability of the phase change thermal conductive composite material, the PDMS-S and PEG@Ag-BNNS / PDMS-S composite materials were placed on a heating table, starting from 25 °C and continuously heated for 360 s. The temperature changes on the surface of the composite materials were observed and recorded using an infrared thermal imager ( Figure 5 a), the curve of its surface temperature changing with time is shown in Figure 5 As shown in b, Figure 5 c is a schematic diagram of the heat dissipation device.

[0125] It can be seen that after 360s of heating, the surface temperature of PDMS-S increased to 81.1°C, while the surface temperature of PEG@Ag-BNNS / PDMS-S phase change thermal conductive composite material only increased to 75.3°C, which was 5.8°C less than that of PDMS-S. This indicates that the phase change thermal conductive composite material with a core-sheath structure has better temperature regulation ability, which is mainly due to the synergistic effect of the thermal conductive sheath layer and the phase change core layer.

[0126] In addition, it can be seen from the temperature-time curve that PEG@Ag-BNNS / PDMS-S has a temperature platform stage in the range of 50 to 60 °C during the heating process, which indicates that a phase change occurs during the heating process, and the material can absorb heat to keep the temperature constant.

[0127] (4) Phase change characteristics of phase change thermal conductive composite materials:

[0128] The phase change properties of PEG2000, PEG@PDMS-S, PEG@h-BN / PDMS-S and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composites were analyzed by DSC. The melting temperatures (T m ), melting enthalpy (ΔH m ) (also called phase change enthalpy), crystallization temperature (T c ), crystallization enthalpy (ΔH c ) See Table 1 and Figure 6 .

[0129] Table 1 Melting temperatures (T) of PEG2000 and PEG@Ag-BNNS / PDMS-S composites m ), melting enthalpy (ΔH m ), crystallization temperature (T c ) and crystallization enthalpy (ΔH c )

[0130]

[0131] As shown in Table 1, the T m and T c 57.5℃ and 27.3℃ respectively, ΔH m and ΔH c 94.1 J / g and 94.6 J / g, respectively, while the T of PEG@Ag-BNNS / PDMS-S m and T c 58.9℃ and 25.2℃ respectively, ΔH m and ΔH c Compared with pure PEG2000, the T m Slightly increased, T c It is slightly lower, indicating that the melting and crystallization of the phase change material are delayed after being encapsulated by the encapsulation layer. At the same time, compared with pure PEG2000, the ΔH m and ΔH cThis is mainly because the content of PEG2000 that provides the latent heat of phase change in the composite material is reduced (PEG2000 accounts for 40.7wt% of the composite material), which reduces the source of phase change enthalpy generation, but the composite material still retains 69.5% and 64.8% of ΔH m and ΔH c The results show that the phase-change thermal conductive composite material with core-sheath structure can not only effectively encapsulate PEG2000 and prevent its leakage, but also better maintain the phase change characteristics of PEG2000. The T m Slightly lower, T c It increases slightly, indicating that the good thermal conductivity of the shell is beneficial to improving the hysteresis of the phase change process of the core material after encapsulation.

[0132] from Figure 6 It can be seen from the DSC curves of PEG2000 and PEG@Ag-BNNS / PDMS-S composites shown in a that both PEG2000 and PEG@Ag-BNNS / PDMS-S phase change thermal conductive composites showed a well-shaped single melting / crystallization peak during the heating and cooling processes, indicating that PEG2000 maintained good phase change behavior before and after compounding.

[0133] After 50 cycles of hot and cold, the DSC curve of the composite material still maintains a good shape ( Figure 6 b), its ΔH m It is 95.4% of the original one, showing excellent cycle stability.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A modified boron nitride nanosheet, characterized in that: The modified boron nitride nanosheets are boron nitride nanosheets whose surfaces are functionalized with bio-based polyphenols and modified with Ag nanoparticles, which are recorded as Ag-BNNS.

2. The modified boron nitride nanosheet according to claim 1, characterized in that: The modified boron nitride nanosheet has a lateral size of 1 to 3 μm and a thickness of 5 to 20 nm; The bio-based polyphenols include at least one of catechol, apple polyphenols, tannins and flavonoids.

3. A method for preparing modified boron nitride nanosheets, characterized in that: The following steps are involved: h-BN was dispersed in the aqueous solution of bio-based polyphenols and Ag + The aqueous solution mixture is ball-milled, centrifuged and dried to obtain modified boron nitride nanosheets Ag-BNNS.

4. The method according to claim 3, characterized in that The bio-based polyphenols include one or more of catechol, apple polyphenols, tannins, and flavonoids; and / or In the mixed solution, 0.02-0.1 g / mL Ag + The aqueous solution is mixed with a 0.1-0.4 g / mL aqueous solution of bio-based polyphenols in a volume ratio of 1:1; and / or Preferably, the solubility of h-BN in the mixed solution is 0.05-0.5 mg / L; and / or Preferably, the dispersion includes uniform dispersion by ultrasonication for 20-120 min; and / or Preferably, the ball milling comprises ball milling in a ball mill at 200 to 500 rpm for 12 to 48 hours; and / or Preferably, the centrifugation comprises centrifugation at 9000-12000 rpm for 10-20 min; and / or Preferably, the drying comprises drying at 60-100° C. for 10-24 h.

5. The modified boron nitride nanosheets prepared by the method as claimed in claim 1 or 2, or the method as claimed in claim 3 or 4 are used in thermal conductive materials.

6. A phase-change thermally conductive composite material having a core-sheath structure, characterized in that: The phase-change thermal conductive composite material comprises a sheath layer and a core layer, wherein the core layer is encapsulated in the sheath layer, wherein: The core layer is made of phase change material. The sheath layer is an encapsulation layer of Ag-BNNS / PDMS-S, and the Ag-BNNS / PDMS-S is a sheath layer ink prepared by modified boron nitride nanosheets Ag-BNNS and terminal vinyl polydimethylsiloxane PDMS. The modified boron nitride nanosheets Ag-BNNS are modified boron nitride nanosheets prepared by the method described in claim 1 or 2, or as described in claim 3 or 4.

7. The phase-change thermally conductive composite material with a core-sheath structure according to claim 6, characterized in that: The phase change material comprises at least one of polyethylene glycol PEG2000, polyethylene glycol PEG1000, paraffin, and long-chain alkane; and / or Preferably, in the phase change thermal conductive composite material, the encapsulation rate of the phase change material reaches 20-80%; and / or Preferably, the thermal conductivity of the phase-change thermally conductive composite material is ≥0.60 W·m -1 ·K -1 , further, thermal conductivity ≥ 0.65 W·m -1 ·K -1 ; and / or Preferably, the phase change enthalpy ΔH of the phase change thermal conductive composite material is m ≥40J / g, further, phase change enthalpy ΔH m ≥65J / g.

8. A coaxial DIW printing preparation method for a phase change thermal conductive composite material with a core-sheath structure, characterized in that: The following steps are involved: (1) Preparation of sheath ink The polymer matrix ink for DIW is prepared by preparing vinyl-terminated polydimethylsiloxane (PDMS) and an active diluent, and its rheological properties are adjusted by using fumed silica, which is recorded as PDMS-S; modified boron nitride nanosheets Ag-BNNS, a photoinitiator and a thermal initiator are added to the PDMS-S, and the mixture is placed in a ball mill and mixed evenly to prepare a sheath ink for DIW printing, which is recorded as Ag-BNNS / PDMS-S; the modified boron nitride nanosheets Ag-BNNS are modified boron nitride nanosheets prepared as described in claim 1 or 2, or as described in claim 3 or 4; (2) Preparation of phase change thermal conductive composite materials The sheath ink Ag-BNNS / PDMS-S is loaded into the outer channel of the coaxial printing needle, and the phase change material enters the inner channel of the coaxial printing needle through the injection pump and is printed in a DIW 3D printer. During the printing process, the extruded sheath ink is in-situ cured by ultraviolet light curing to obtain a phase change thermal conductive composite material with a core-sheath structure with phase change material as the core layer and Ag-BNNS / PDMS-S as the encapsulation layer.

9. The method according to claim 8, characterized in that In step (1), the mass ratio of the vinyl-terminated polydimethylsiloxane (PDMS) to the reactive diluent is 2:1 to 1:2; and / or Preferably, in step (1), the active diluent comprises at least one of IBOA, TPGDA and GMA; and / or Preferably, in step (1), the amount of modified boron nitride nanosheets Ag-BNNS in the sheath ink is 20-40wt%; and / or Preferably, in step (1), the photoinitiator comprises at least one of 819, 1173, 784; and / or Preferably, in step (1), the photoinitiator is 1-4 wt% of the reactive diluent; and / or Preferably, in step (1), the thermal initiator comprises at least one of BPO, AIBN, and ABVN; and / or Preferably, in step (1), the thermal initiator is 1-3 wt % of PDMS; and / or Preferably, in step (2), the outside of the syringe pump has a heating jacket, the temperature of which is set to 50-100° C., so that the phase change material is heated to a liquid so that it is extruded from the coaxial printing needle; Preferably, in step (2), the weight ratio of the phase change material to Ag-BNNS / PDMS-S is 1:4-4:1; and / or Preferably, in step (2), the printed phase change thermal conductive composite material is further cured by keeping the temperature at 80-120° C. for 2-10 hours.

10. The phase change thermal conductive composite material with a core-sheath structure prepared by the method of claim 6 or 7, or claim 8 or 9, is applied to the field of thermal management. Preferably, the thermal management includes the fields of battery thermal management, building energy conservation or communication equipment heat dissipation.

Citation Information

Cited By

  • Hexagonal boron nitride loaded silver nanoparticle hybrid filler, ANF composite material and preparation method

    CN120137267A